Synthesis and Antimicrobial Evaluation of Potent N-Hydroxy-2,4-diaryl-3-azabicyclo[3.3.1]nonan-9-ones and Their Oximes - BASKAR, G.; GOPALAKRISHNAN, M. (Asian Journal of Chemistry, 2010)
N-Hydroxy-2,4-diaryl-3-azabicyclo[3.3.1]nonan-9-ones [2a- 2c] obtained by the reaction between the 2,4-diaryl-3- azabicyclo[3.3.1]nonan-9-ones [1a-1c] and m-chloroperbenzoic acid, then N-hydroxy-2,4-diaryl-3-azabicyclo[3.3.1]nonan-9-one oximes [3a-3c] obtained by the reaction between N-hydroxy-2,4- diaryl-3-azabicyclo[3.3.1]nonan-9-one and hydroxyl amine hydrochloride are screened against selected bacteria (Vibro cholerae, Salmonella typii, Shigella flexneri, Escherichia coli, Staphylococous aureus, Klebsiella pneummonia, β-Heamolytic streptococcus and Pseudomonas) and fungi (Aspergillus flavus, Mucor, Microsporum gypseum and Rhizopus). Disc diffusion method is employed to determine the in vitro antibiotic effect. The inhibitory effects of the compounds are very close and identical in magnitude and are comparable with that of the standard antibiotic used.